2019
DOI: 10.21276/ijcmr.2019.6.4.45
|View full text |Cite
|
Sign up to set email alerts
|

Candida Species Isolation, Identification and Biofilm Detection at a Tertiary Care Hospital

Abstract: Introduction:Early diagnosis and accurate treatment of candida infected patients helps to reduce the risk of infection and improves patient outcome. Candida isolation, speciation and its invasiveness can be determined by culture, antigen and antibody estimation, glucan estimation and PCR. The present study aimed at candida isolation, speciation and detection of biofilm production among various clinical samples. Material and Methods: Various clinical samples such as urine, pus, blood, cerebrospinal fluid, body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…According to the findings of the Centers for Disease Control and Prevention, Candida infections are held responsible for 11% of all nosocomial infections. Candida albicans remains the leading cause of Candida bloodstream infections; however, the prevalence of non albicans Candida infections has increased worldwide, particularly C. tropicalis, C. glabrata, C. parapsilosis and C. krusei as seen by Bac N.D et al 12 In this study, most of the Candida isolates were found to be higher in male patients (55.10%) as compared to female patients (44.8%).This correlates well with the study of RA Kashid et al in 2011 who reported that the isolation of Candida species were higher in males (55.10%) as compared to females (44.8%) with male to female ratio of 1:0.81 and Renuka Devi et al 13 in which 54.6% were in males and 45.3% in females. Unlike this study from Amar C.S et al 14 in 2013, isolated Candida species were more from female(60.2%) than male (39.8%) patients in ratio of 0.6:1 (M>F).…”
Section: Discussionsupporting
confidence: 91%
“…According to the findings of the Centers for Disease Control and Prevention, Candida infections are held responsible for 11% of all nosocomial infections. Candida albicans remains the leading cause of Candida bloodstream infections; however, the prevalence of non albicans Candida infections has increased worldwide, particularly C. tropicalis, C. glabrata, C. parapsilosis and C. krusei as seen by Bac N.D et al 12 In this study, most of the Candida isolates were found to be higher in male patients (55.10%) as compared to female patients (44.8%).This correlates well with the study of RA Kashid et al in 2011 who reported that the isolation of Candida species were higher in males (55.10%) as compared to females (44.8%) with male to female ratio of 1:0.81 and Renuka Devi et al 13 in which 54.6% were in males and 45.3% in females. Unlike this study from Amar C.S et al 14 in 2013, isolated Candida species were more from female(60.2%) than male (39.8%) patients in ratio of 0.6:1 (M>F).…”
Section: Discussionsupporting
confidence: 91%
“…albicans in terms of incidence and attributable mortality [ 25 , 31 , 34 , 42 , 48 51 ]. This new scenario could be attributed to the implementation of better molecular techniques in the identification of Candida species [ 21 , 29 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…is the most common cause of a wide range of superficial infections of mucosal surfaces in humans, it colonizes the gastrointestinal and reproductive systems, particularly the female vaginal tract, as well as the skin (Alfouzan and Dhar, 2017). Immunosuppressive disorders such as diabetes, HIV, chemotherapy patients, take broad-spectrum antibiotics or steroids, and indwelling medical equipment implanted in the body such as urinary catheters are all risk factors for invasive Candida infections (Devi et al, 2019). There are several factors that may lead to candiduria in diabetic patients such as female gender and uncontrolled diabetes (Geerlings et al, 2014).…”
Section: Introductionmentioning
confidence: 99%